Resilience in the Changed Conditions of Educational and Professional Training of Future Specialists of a Socionomic Profile - Koval , Oleksii; Fomina , Iryna; Golub , Iuliia; Ozerov , Denys (Insight: the psychological dimensions of society, 2024)
The aim is to research the relationship between respondents’ resilience and key indicators of educational and professional training in the changed conditions of the educational environment. The sample was made up of first- and second-level higher education students studying at Ukrainian universities, who belong to future specialists in a socionomic profile, and at the time of the study, the educational process of these universities underwent significant transformational changes. General sample parameters: number of respondents (n=243); age range – from 18 to 36 years; descriptive frequency characteristics of age (M=22.43; SD=4.91; Me=22.50). Methods. Valid and reliable psychodiagnostic tests were applied: “Resilience Scale” (CD-RISC-10) (Connor & Davidson, 2003); the “Dispositional characteristics of personality self-development” (DCPS) (Kuzikova, 2017); questionnaire “Hardiness Survey” (Maddi & Khoshaba, 1994) and the grade point average according to the results of the 2022-2023 academic year. Results. It was established that there are no significant differences between the psychological content parameters of resilience, hardiness and key indicators of educational and professional training of bachelors and master’s students according to the Mann-Whitney (U) criterion. It was found that resilience has five statistically significant correlations with the researched parameters (p<.050; p<.010): need for self-development; conditions of self-development; engagement; control; challenge; general level of hardiness. Comparison of low (group I) and high (group II) levels of resilience demonstrated the superiority of group II in five parameters (р<.050; р<.010): need for self-development (U=149.500; p=.000); conditions of self-development (U=134.000; p=.000); mechanisms of self-development (U=198.500; p=.038); general level of self-development (U=178.500; p=.000) and engagement (U=145.500; p=.000). Discussion and сonclusions. It was proven that students with a high level of resilience are able to develop under any circumstances, and negative events, critical situations and changed conditions are perceived by them as another stage of challenge. It was recommended to implement the received scientific facts into teaching, organizational and pedagogical work.